FEASIBILITY ANALYSIS OF ENVIRONMENTALLY FRIENDLY LOCAL DUCK RAISING MICRO BUSINESS BASED ON NATURAL FEED - Ilham Wira Rohmat, Farhan
The micro-business of raising local broiler ducks has advantages over broilers and native chickens, including ease of cultivation, disease resistance, low mortality risk, high growth speed, low seed prices, and high selling value of harvested products. However, there are constraints in terms of dependence on commercial feed (PK) which has a high price and has the potential to harm the environment. This study aims to examine the use of natural-based alternative feeds on the growth performance of ducks and their impact on the environment. The alternative feeds studied were bran (DK), hydroponic maize fodder (HMF), and Black Soldier Fly (BSF) larvae. The results of the next study are the compilation of the best UMKM models. Growth performance testing was carried out on local broiler ducks aged 21 days to 42 days. The treatments used were Treatment A (PK + DK), Treatment B (PK + DK + HMF), Treatment C (PK + DK + BSF), Treatment D (PK + HMF + BSF), Treatment E (HMF + BSF), and Treatment F (PK + DK + HMF + BSF). Parameters measured were weight gain, final weight, and FCR. Test the best treatment results using the ANOVA statistical method. Environmental impact analysis for each treatment uses the Life Cycle Assessment (LCA) method. The environmental impact parameters measured are Global Warming Potential (GWP) and Photochemical Ozone Creation Potential (POCP). The analysis of the feasibility of a micro business is assessed based on the parameters of the NPV, BC Ratio, IRR, and ROI. ANOVA test results showed that the daily weight gain, final weight, and FCR were not significantly different (P> 0.05) where C treatment was the best treatment with the highest daily weight growth value of 1097.5 grams, the highest average final weight was 1275 grams, and The lowest FCR is 3.29. The results of the LCA analysis show that Treatment A has the highest environmental impact with a GWP value of 2.51 kg CO2 / functional unit, POCP of 5.34 x 10-7 kg CH4 / kg of functional unit, and a cost of the environmental impact of IDR. 4,638. Meanwhile, treatment E gave the lowest environmental impact with a GWP value of 1.28 kg CO2 / functional unit, POCP of 3.22 x 10-7 kg C2H6 / kg functional unit, and a cost of the environmental impact of IDR. 2,427. The feasibility analysis of the local broiler duck rearing micro business was carried out based on the use of feed with the lowest environmental impact, namely treatment E. The results of the feasibility analysis of the micro-business showed that local broiler duck rearing was feasible with an NPV value (rate of 10%) of Rp. 3,710,085, PP for less than 2 years, BC Ratio 2.63, IRR of 73.23%, and ROI of 7.76%. The best feed treatment provides a high environmental impact on the air, it is necessary to further study how the environment impacts other environmental factors and how to control these solutions.